VAGINAL BIRTH IN WOMEN WITH A SCAR ON THE UTERUS - Елена Николаевна Кравченко; Лариса Владимировна Куклина; Софья Сергеевна Синицына; Галина Федоровна Рублева; Марина Павловна Владимирова (The Publishing House Medicine and Enlightenment, 2021)
Objective. To analyze the outcomes of childbirth in women with a scar on the uterus after cesarean section and myomectomy. Material and methods. A retrospective analysis of 1633 births in women with a scar on the uterus that occurred in the perinatal center over three years (2018-2020) was carried out. Results. According to Robson's classification, 833 women were assigned to group 5.1, which amounted to 51 % of all those with a scar on the uterus. Group 5.2 included 507 women (31 %). In total, there were 1340 (82.1 %) women who gave birth with a scar on the uterus after KS operation; after myomectomy, there were 293 (17.9 %) patients. 220 pregnant women were prepared for vaginal delivery, while vaginal delivery was performed in 191 pregnant women with a scar on the uterus (86.8 % of the prepared women). A scar on the uterus after one CS operation was observed in 177 (92.1 %) pregnant women, after two CS - in 9 (4.7 %), after myomectomy - in 9 (4.7 %) patients. Conclusion. 86.9 % of women with a scar on the uterus, selected for labor through the vaginal birth canal were successfully delivered. Weakness of labor activity developed in 7.2 % of cases, fetal hypoxia - in 5.9 %, which required a revision of the labor management plan in favor of cesarean section. The results obtained allowed us to conclude that the main reserve for reducing the frequency of CS is the rational selection of patients for induction of labor, delivery of women with a scar on the uterus by the vaginal route.